PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING SEBAGAI MEDIA PENGEMBANGAN PENDIDIKAN KARAKTER BANGSA - Ngatmini . (Universitas PGRI Semarang, 2013)
Learning is a process of gaininga knowledge through learning. The learning process is linfluenced by internal and external factors. Internal factors derives from self-learner and external factor, which is the factor from the out side, derives from parents, society, and school. Teacher is one part of the shool. Thus, teacher?óÔé¼Ôäós decision in determining the learning program will determine the student leaning outcomes. CTL learning is one of leaning that associates learning materials with the life around of student and the enviroment. In the CTL learning, student experience a fun, an inovatif, and a creative learning process, because this learning associated with life around of student. Thus, the knowledge that student acquired can be more meaningful. In the learning by CTL, student required to doing the character learning activities, such as cooperation, responsible, honest, patient, carefull, creative, and inovative. Those value are part of educational value of the nation character. Thus, with CTL learning, educational development of nation character can be imported to the student. Key words: CTL learning, educational of nation character.